Anomalous conductivity behavior induced by in situ metastable amorphous phase in BaTiO3/Ni0.5Zn0.5Fe2O4 ceramic composite. Issue 18 (15th December 2020) - Xiao, Bin; Tang, Yu; Du, Piyi; Wang, Hong
Abstract: The electrical conductivity of ferroelectric-ferromagnetic ceramic composites usually increases monotonously with elevated temperature, which may seriously deteriorate their performance. In this work, we report an anomalous conductivity behavior induced by in situ metastable amorphous phase in a semi-conductive ceramic composite, 0.1BaTiO3 (BTO)/0.9Ni0.5 Zn0.5 Fe2 O4 (NZFO). The ceramic composites with in situ formed amorphous BTO phase (a-BTO) or crystalline BTO phase (c-BTO) were successfully prepared. The effect of such metastable amorphous phase on the electrical transport properties of the ceramic composite was investigated. A comparative study reveals that a-BTO could act as a buffering phase preventing the electrical conductivity of the composite from monotonous increment above a critical temperature (513 K), whereas such effect does not occur when BTO is pure crystalline. Around 513 K, a change in the activation energy of dc conductivity has been observed for the c-BTO/NZFO sample. Whereas for the a-BTO/NZFO sample, the Arrhenius relation fails to describe its behavior above 513 K owing to decreased conductivity, which is rarely seen in semiconductors. The activation energy of relaxation is identical for both systems, i.e. 0.204 eV, because their dielectric relaxation is dominated by crystalline NZFO phase. The findings of this work are inspiring for the design of novel electronic materials constituted by a crystalline phase and an amorphous phase with adjustable performance.